Enhancement of Mechanical Properties of Hybrid Polymer Composites Using Palmyra Palm and Coconut Sheath Fibers: The Role of Tamarind Shell Powder - Karthik Aruchamy; Manickaraj Karuppusamy; Sivasankari Krishnakumar; Sivasubramanian Palanisamy; Manivannan Jayamani; Kumar Sureshkumar; Syed Kashif Ali; Saleh A. Al-Farraj (BioResources)
This study investigates the enhancement of mechanical characteristics of hybrid polymer composites reinforced with Palmyra Palm Leaflet (PPL) and Coconut Sheath Leaf (CSL) fibers by integrating Tamarind Shell Powder as a filler material. The composites were fabricated with varying ratios of PPL and CSL fibers, and their tensile strength, flexural strength, interlaminar shear strength (ILSS), impact strength, hardness, and water absorption were evaluated. Results indicated that the composite with 20% PPL and 10% CSL exhibited superior mechanical performance, achieving the highest tensile strength of 42.22 MPa, flexural strength of 94.35 MPa, ILSS of 7.52 MPa, and impact strength of 5.98 J. Hardness values peaked at 84.12 SD for the same composition. Moreover, the integration of Tamarind Shell Powder significantly improved the mechanical properties compared to composites without filler, which showed lower values across all parameters. Water absorption tests revealed an increase in water uptake with filler incorporation, though within acceptable limits for practical applications. Scanning Electron Microscopy (SEM) analysis further supported these results by revealing enhanced fiber-matrix bonding and better dispersion of the filler, resulting in fewer voids and defects. This research highlights the potential of bio-based fillers in optimizing the mechanical performance of hybrid composites for sustainable engineering applications.